Cultural History: Where It Has Been and Where It Is Going. Issue 1 (28th March 2018) - Applegate, Celia; Potter, Pamela
Abstract : The very meaning of "culture" has gone through so many transformations over the last sixty years that it is necessary to take stock of developments in this field of cultural history before suggesting—with an eye to the promises and perils of earlier practices—what new possibilities might exist for the future of the field. The post-1945 period witnessed a powerful impulse to understand culture as something more pervasive than just literature and the arts—and as something more socially and politically reverberant than the shibboleth of "art for art's sake." In 1957, at the very beginning of the modern practice of cultural history, Richard Hoggart's The Uses of Literacy found the high and low hierarchies embedded in it. It focused on working-class culture (e.g., glossy magazines, films, "penny dreadfuls"), and on how reading was changing under the impact of mass media. By 1976, Raymond Williams needed to draw attention to the complexity of the word culture, so extended had its purview become over the previous two decades. Linda Nochlin asked why they were no great women artists, and T. J. Clark, using a Marxist framework, sought to understand aesthetic modernism by interrogating the historic circumstances that had led to the breakdown of the academic system. The New Cultural History, edited by Lynn Hunt, came out in 1989. Its "models" for cultural history were the work of Michel Foucault, Clifford Geertz, Natalie Zemon Davis, E. P. Thompson, Hayden White, and Dominick LaCapra, and its "new approaches" came from Mary Ryan, Roger Chartier, Thomas Laqueur, and Randolph Starn. These scholars were legislators of discourse and narrative, of popular and working-class culture, of gender, epistemes, and thick description. With many other tendencies, often defined by their focus on theoretical explication and elaboration, these approaches had the effect of deterring scholars from reengaging with the traditional interests—even the raison d'etre —of cultural history, namely, art, architecture, theater, dance, music, and literature. This turning-away also affected the very composition of humanities and interpretive social science departments, which added many new subjects of study but, inevitably perhaps, let others wither away.